The Importance of Innovative Technologies and Interactive Methods in Teaching English to Students - Boboyeva Maftuna Qurbon qizi (Genius Publishing Group, 2024)
This article analyzes the views of scholars and educators on the scientific and theoretical aspects of teaching English to students through innovative technologies and interactive methods and the factors that stimulate their interest in learning the language, and their subjective attitudes.
Keywords: independent teaching technologies; foreign language teaching methodology; worldview; thinking